A Comprehensive Systematic Review of Data Linkage Publications on Diabetes in Australia - Ngan T. T. Dinh; Ngan T. T. Dinh; Ingrid A. Cox; Barbara de Graaff; Julie A. Campbell; Brian Stokes; Andrew J. Palmer; Andrew J. Palmer (Frontiers Media S.A., 2022)
AimsOur study aimed to identify the common themes, knowledge gaps and to evaluate the quality of data linkage research on diabetes in Australia.MethodsThis systematic review was developed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (the PRISMA Statement). Six biomedical databases and the Australian Population Health Research Network (PHRN) website were searched. A narrative synthesis was conducted to comprehensively identify the common themes and knowledge gaps. The guidelines for studies involving data linkage were used to appraise methodological quality of included studies.ResultsAfter screening and hand-searching, 118 studies were included in the final analysis. Data linkage publications confirmed negative health outcomes in people with diabetes, reported risk factors for diabetes and its complications, and found an inverse association between primary care use and hospitalization. Linked data were used to validate data sources and diabetes instruments. There were limited publications investigating healthcare expenditure and adverse drug reactions (ADRs) in people with diabetes. Regarding methodological assessment, important information about the linkage performed was under-reported in included studies.ConclusionsIn the future, more up to date data linkage research addressing costs of diabetes and its complications in a contemporary Australian setting, as well as research assessing ADRs of recently approved antidiabetic medications, are required.